The Juridical Review of Notaries Who Actually As State Officers in the Concept of Legal Assurance - Rindra Agung Wiguna (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
In legal research, legal theory becomes a scalpel to analyze problems using legal certainty theory and liability theory. This study uses three (3) sources of data, namely legal materials, namely primary, secondary and tertiary legal materials, while data collection techniques use library research. Data analysis using qualitative analysis method using deductive logic and described analytically descriptive. The results of the research found the rules regarding the prohibition of a Notary concurrently serving as a state official in Article 17 paragraph (1) letter d of Act No. 2 of 2014 concerning amendments to Act No. 30 of 2004 concerning Notary Positions. So it can be concluded that a Notary concurrently serving as a state official is a violation of the law, the Notary Supervisory Board has the right to conduct an examination of alleged violations and impose sanctions on a Notary if proven to have committed a violation.